Challenging Leadership Stereotypes through Discourse : Power, Management and Gender - Ilie, Cornelia; Schnurr, Stephanie (Springer Singapore : Imprint: Springer, 2017)
This multidisciplinary volume brings together wide-ranging empirical research that goes behind the scenes of diverse organizations dealing with business, politics, law, media, education, and sports to unravel stereotypes of discursive leadership practices as they unfold in situ. It includes contributions that explore how leadership discourse is impacted by increasing pressures of "glocalisation" (the need to communicate across cultures and languages), "mediatisation" (leaving ubiquitous digital traces), standardization (with quality management programmes negotiating organizational procedures), mobility (endless fast-paced long distance synchronization) and acceleration (permanent co-adaption and change). The discussion of purposefully chosen case studies moves beyond questions of who is a leader and what leaders do, to how leadership stereotypes are being challenged in various communities of practice, and thereby making change possible. Cross-cultural and interdisciplinary approaches are used to get deeper insights into the competing, multi-voiced, controversial and complex identities and relationships enacted in leadership discourse practices. "This volume is a must-read for anyone interested in leadership discourse. Focusing on the under-researched area of stereotyping, it offers a fresh and much-needed perspective." -Louise Mullany, Professor, Faculty of Arts, University of Nottingham, UK "A timely and highly recommendable contribution to the leadership field, clearly demonstrating the value of taking discourse seriously and exploring it in depth!" -Magnus Larsson, Associate Professor, Department of Organization Copenhagen Business School, Denmark "Cornelia Ilie and Stephanie Schnurr have edited an exciting volume with incisive analysis that grounds leadership in issues of power, context, meaning, and interaction process." -Gail Fairhurst, Distinguished University Research Professor University of Cincinnati, USA.